Evaluating the reliability of the athlete sleep behavior questionnaire (ASBQ): a meta-analysis of Cronbach`s alpha and intraclass correlation coefficient - Trabelsi, K.; Saif, Z.; Driller, M. W.; Vitiello, M. V.; Jahrami, H. (BMC Sports Science, Medicine and Rehabilitation, 2024)
Background The Athlete Sleep Behavior Questionnaire (ASBQ) was designed to identify maladaptive sleep practices among athletes. The aim of this meta-analysis was to evaluate the internal consistency and the test-retest reliability coefficients of the ASBQ.